Expert System in Diagnosing Pet Disease - Jusoh, Suffian; Ab.Aziz, Ruhaya (Applied Information Technology And Computer Science, 2023)
The existing system of the Klinik Haiwan & Surgeri (MHI) are not appropriate because of the pet owner need to fill the registration form every time their pet get a treatment. MHI also use unappropriated method to give the consultation about the pet treatment and medicine intake method by the phone call. The purpose of MyPet are to help the owner to diagnosis the pet disease by selecting the symptoms in the phone. This system developed to change the method of consultation session to appropriate one and the user will get the benefits from this expert system that uses the rule base inference engine in diagnosis their pet disease. The result that obtains from system analysis and design using object-oriented approach, Use Case diagram, Class diagram, To-be model flowchart have been developed. Lastly, system prototype has been developed to make sure that the system fulfills the all the requirements.